Effectiveness of Combination of Massage with Ginger Oil and Exercise on Joint Pain in the Elderly - Lina Puspitasari (Indonesian Journal of Global Health Research, 2023)
Joint pain in the elderly is still not resolved independently in the community. When the elderly do heavy workloads, the joint capsule ruptures, and the collagen present in the connective tissue increases progressively. The result can be inflammation and pain in the joint area. So it needs independent treatment using non-pharmacological management in the form of massage and ginger compresses. Objective to elderly with complaints of joint pain and without complications. This study used an experimental method to compare before and after skeletal muscle massage and ginger compress for joint pain in the elderly. The subjects in the study consisted of a population of 20 respondents and a sample of 20 respondents. This research was conducted in the Tritih Kulon Region, Cilacap Regency from March to May 2021. Samples were taken using purposive sampling. The analysis of this study used the t-test. The result is that t count > t table, namely t count 9.886 and t table 2.045, then Ho is rejected and Ha is accepted. This means that there are benefits of skeletal muscle massage and ginger compresses for joint pain in the elderly. The conclusion from this study is that there are benefits of skeletal muscle massage and ginger compresses for joint pain in the elderly.